2018
DOI: 10.1038/s41598-018-25725-w
|View full text |Cite
|
Sign up to set email alerts
|

The Protease Activated Receptor2 Promotes Rab5a Mediated Generation of Pro-metastatic Microvesicles

Abstract: Metastasis, the hallmark of cancer propagation is attributed by the modification of phenotypic/functional behavior of cells to break attachment and migrate to distant body parts. Cancer cell-secreted microvesicles (MVs) contribute immensely in disease propagation. These nano-vesicles, generated from plasma membrane outward budding are taken up by nearby healthy cells thereby inducing phenotypic alterations in those recipient cells. Protease activated receptor 2 (PAR2), activated by trypsin, also contributes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Based on both in vitro and in vivo observations, we and several other groups have already established that TF and PAR2 are over-expressed in highly aggressive breast cancer cells (10,16,27,28). In our previous investigations (11), we have demonstrated that PAR2 activation by TF-FVIIa or trypsin leads to pro-metastatic MV generation from the human TNBC cell, MDAMB231, which has also been represented here as shown in Fig.…”
Section: MV Generated From Mdamb231 Induce Emt In Mcf7 Via Akt/nf-b mentioning
confidence: 52%
See 3 more Smart Citations
“…Based on both in vitro and in vivo observations, we and several other groups have already established that TF and PAR2 are over-expressed in highly aggressive breast cancer cells (10,16,27,28). In our previous investigations (11), we have demonstrated that PAR2 activation by TF-FVIIa or trypsin leads to pro-metastatic MV generation from the human TNBC cell, MDAMB231, which has also been represented here as shown in Fig.…”
Section: MV Generated From Mdamb231 Induce Emt In Mcf7 Via Akt/nf-b mentioning
confidence: 52%
“…The exposure of human TNBC cells, MDAMB231 to hypoxia, results in the liberation of MV in a Rab22A-dependent manner, which is capable of promoting focal adhesion formation, invasion, and metastasis to the neighboring recipient cells (27). In the recent past, we have shown that activation of PAR2 by coagulation factors induces prometastatic MV generation from human TNBC cells (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of these sequential events results in a fewer MVs count in the cell supernatant suggesting their definite role in PAR2‐mediated MVs generation process. In an earlier report, we have demonstrated that Trypsin‐mediated PAR2 activation results in MVs shedding from MDAMB231 cell surface via Rab5a‐dependent polymerization of actin . Knock‐down of Rab5a or treatment of the cells with its dominant‐negative (DN) form impairs both Trypsin‐induced actin polymerization as well as subsequent MVs generation.…”
Section: Discussionmentioning
confidence: 94%